2018
DOI: 10.1029/2018gl080399
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Submesoscale Ageostrophic Motions Through the Life Cycle of Oceanic Mesoscale Eddies

Abstract: The global ocean circulation is forced by large‐scale fluxes at the surface and dissipated at small scales by diffusion. To achieve a long‐term equilibrium requires a dynamical route that transfers energy from large to dissipative scales. The submesoscale ageostrophic motions (1–50 km) have been hypothesized recently to play a critical role in this route by extracting energy from mesoscale eddies (50–500 km) that contain the majority of oceanic kinetic energy. By combining global surface velocity measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 42 publications
4
44
0
Order By: Relevance
“…It should be noted that the ground tracks of currently operating altimeter satellites are unable to resolve relatively small-scale geostrophic signals and potentially introduce errors in the ageostrophic velocity estimation. It has, however, been shown that this does not substantially bias the results when investigating the ageostrophic motions and their relation to geostrophic strain rates 30 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that the ground tracks of currently operating altimeter satellites are unable to resolve relatively small-scale geostrophic signals and potentially introduce errors in the ageostrophic velocity estimation. It has, however, been shown that this does not substantially bias the results when investigating the ageostrophic motions and their relation to geostrophic strain rates 30 .…”
Section: Resultsmentioning
confidence: 98%
“…Nowadays, the number of global positioning system (GPS)-tracked surface drifters is large enough to achieve a global coverage and can provide accurate real-time position time series 2428 . With a typical sampling interval at about 6 h, the drifters are able to resolve the submesoscale ageostrophic velocity signals at the sea surface globally; this includes both the unbalanced wave motions 29 and submesoscale balanced ageostrophic motions 27,30 .…”
Section: Introductionmentioning
confidence: 99%
“…The mesoscale eddies contain the majority of the oceanic kinetic energy and the remaining question to answer is how the mesoscale eddies in geostrophic balance transfer energy to smaller scales, where the energy can be dissipated irreversibly. It is believed that ageostrophic motions play a critical role in this process [47]. Thus, it is important to examine the degree of the geostrophy.…”
Section: Geostrophymentioning
confidence: 99%
“…Elipot et al () produced a unique global data set of surface drifter positions and velocities with hourly temporal resolution, which enables studies of near‐surface high‐frequency motion (e.g., inertial and tidal). The surface drifter measurements have been previously used to investigate a wide range of oceanic processes and dynamics, from global velocity climatology (Lumpkin & Johnson, ) and mesoscale coherent vortices (Lumpkin, ) to submesoscale motions (Lumpkin & Elipot, ; Zhang & Qiu, ), near‐inertial waves (Elipot et al, ; Liu et al, ), internal tides (Zaron, ), and relative dispersion (Corrado et al, ). In situ observations by oceanographic moorings or profiling instruments may be suited to obtaining depth‐dependent tidal and higher‐frequency variability for model assessment (e.g., Ansong et al, ; Savage et al, ) and thus complement surface drifter observations.…”
Section: Introductionmentioning
confidence: 99%